Evaluation of interleukin 23 (IL-23) as a non-invasive test of disease severity in patients with ulcerative colitis - Youssef, Tarek; Saleh, Shereen A.; Rund, Angie; Montasser, Iman; Mohsen, Manal; Hazem, Ola (Arab journal of gastroenterology, 2018)
Studies have found increased expression of IL-23 in inflamed and non-inflamed mucosa of patients with ulcerative colitis (UC). We hypothesized that serum interleukin-23 as a non-invasive test has a role in pathogenesis of ulcerative colitis disease and correlates with the disease severity. Forty patients with biopsy proven ulcerative colitis, recruited from Ain Shams University hospitals were included. Forty healthy subjects matched in age and gender were also included in the study as a control group. Serum IL-23 level was quantified using quantitative ELISA technique (Enzyme linked Immunosorbent Assay). Patients with UC had higher level of interleukin 23 (234.5 ± 161 pg/mL) compared to control subjects (54.2 ± 15 pg/mL) and the level of IL-23 correlated with the disease severity. Cut off value of IL-23 at 68 pg/mL was the best to differentiate between cases and control subjects. Receiver operating characteristic curve (ROC) revealed that the best cut off for IL-23 to detect mild cases of ulcerative colitis was at105 pg/mL, to detect moderate cases at 200 pg/mL and to detect severe cases was at 270 pg/mL with sensitivity 80% to mild cases, 60% to moderate cases and 81% to severe cases. Our findings confirm the suggestion that IL-23 level measurement may be of value as a non-invasive test in the diagnosis and disease severity assessment in patients with UC.